Vitrectomized versus non-vitrectomized eyes in diabetic macular edema response to ranibizumab—retinal layers thickness as prognostic biomarkers - Bernardete Pessoa (Nature Portfolio, 2021)
Abstract To evaluate the role of the vitreous in the management of diabetic macular edema with ranibizumab intravitreal injections in a pro re nata regimen. Prospective study of 50 consecutive eyes with diabetic macular edema treated with ranibizumab and 12 months of follow-up. Primary endpoint: to assess differences between non-vitrectomized and vitrectomized eyes in the number injections needed to control the edema. Secondary endpoints: comparison of groups regarding best corrected visual acuity, central foveal thickness and thickness of seven retinal layers. 46 eyes from 38 patients, 10 vitrectomized and 36 non-vitrectomized, completed the follow-up. At month 12, the two groups achieved an equivalent anatomical outcome and needed a similar number of ranibizumab intravitreal injections. In vitrectomized eyes final visual acuity was worse when baseline retinal nerve fiber layers in the central foveal subfield were thicker, showing a strong correlation (r = − 0.942, p < 0.001). A similar, albeit moderate correlation was observed in non-vitrectomized eyes (r = − 0.504, p = 0.002). A decrease of retinal nerve fiber layers inner ring thickness was correlated with a better final visual acuity only in vitrectomized eyes (r = 0.734, p = 0.016). The effect of diabetic macular edema seems to be worse in vitrectomized eyes, with a thinner inner retina reservoir. Clinicaltrials.govNCT04387604.